Islam and the Environment (A Study of Durian Skin Waste as an Adsorbent to overcome Water Pollution) - Rahmiani Gani (Al-Hikmah Journal for Religious Studies, 2022)
Nowadays environmental pollution has become a serious problem. Textile dye waste is one of the biggest contributors to environmental pollution. Durian (Durio zibethinus) has been known as a popular fruit in Indonesia. However, only several part of the durian fruit is used, namely its flesh. Durian skin is generally only thrown away and becomes waste pollutes the environment. Durian skin waste can be used as activated carbon in overcoming textile dye waste pollution. This study aims to determine the potential of durian skin from Luwu Regency, South Sulawesi as an adsorbent for textile dye waste. The process of making activated carbon is carried out through two stages that is physically by heating at 600 oC and chemically with hydrochloric acid 1M as activator and stirring for 24 hours. The quality test of activated carbon includes tests for water content, ash content, volatile matter content and fixed carbon content. The results showed that the activated carbon of the durian skin had met the standards of SNI 06-3730-1995, namely water content 12.1%, ash content 0.2%, volatile matter content 27.3% and bound carbon content 72.5%.